MOBILE BANKING SYSTEM - Ahmad Syarief Iskandar; Tadjuddin Tadjuddin; Lesti Lesti; Rahmat Rahmat (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2020)
This study aims to determine the effect of benefit, ease of use, and risk on interest in using mobile banking among the people of Suli Village communities in Luwu District. The sample of this research is the Suli Village communities; the technique used by the author is purposive sampling. The research method used is quantitative research methods and analysis using multiple regression models and processed using SPSS 15. The results showed that based on the simultaneous test (F test) conducted; the F-count was 112,364 with a significance level (0.00 < 0.05), where it was known that the F-count > F-table (112,364 > 2.70). In contrast, the partial test (t-test) was carried out that the user had a significant effect on the interest in using mobile banking where t-count was 5.472 with a significant value (0.000 < 0.05), where it was known that the value of t-count > t-table (5.472 > 1.98498). In contrast, the partial test on ease of use has a significant effect on interest in using mobile banking where t-count is 2.825 with a significant value (0.125 < 0.05), it is known that the value of t-count > t-table (2.825 > 1.98498). Partially, the risk does not affect the interest in using mobile banking where t-count is 0.945 with a significant value of 0.125 <0.05, where it is known that t-count < t-table (0.945 <1.98498). The implications of the results of this study are relevant for people interested in using mobile banking to pay more attention to the benefits, convenience, and risk factors. Mobile banking users are expected to be more confident that using mobile banking can facilitate their banking activities. In particular, people who are still far from accessing public services, namely ATMs or banks, can be helped by mobile banking to save time, energy, and costs.